Association between GWAS-Identified Genetic Variations and Disease Prognosis for Patients with Colorectal Cancer - Kang, Byung Woog (PLoS One, 2015)
Genome-wide association studies (GWASs) have already identified at least 22 common susceptibility loci associated with an increased risk of colorectal cancer (CRC). This study examined the relationship between these single nucleotide polymorphisms (SNPs) and the clinical outcomes of patients with colorectal cancer. Seven hundred seventy-six patients with surgically resected colorectal adenocarcinoma were enrolled in the present study. Twenty-two of the GWAS-identified SNPs were genotyped using a Sequenom MassARRAY. Among the 22 SNPs, two (rs1321311G>T in CDKN1A and rs10411210C>T in RHPN2) were significantly associated with the survival outcomes of CRC in a multivariate survival analysis. In a recessive model, the rs1321311 TT genotype (vs. GG + GT) and rs10411210 TT genotype (vs. CC + CT) were associated with a worse prognosis for disease-free survival (adjusted HR = 1.90; 95% confidence interval = 1.00-3.60; P = 0.050, adjusted HR = 1.94; 95% confidence interval = 1.05-3.57; P = 0.034, respectively) and overall survival (adjusted HR = 2.05; 95% confidence interval = 1.00-4.20; P = 0.049, adjusted HR = 2.06; 95% confidence interval = 1.05-4.05; P = 0.036, respectively). None of the other SNPs was significantly associated with any clinicopathologic features or survival. The present results suggest that the genetic variants of the CDKN1A (rs1321311) and RHPN2 (rs10411210) genes can be used as prognostic biomarkers for patients with surgically resected colorectal cancer.